Red light perovskite material based on bromine-iodine mixed halogen and preparation method thereof

By introducing doped metal elements into red light perovskite materials and using high-temperature solid-state calcination method, the problems of material composition unevenness and halogen ion migration are solved, the composition uniformity and stability of the material are achieved, and the photofluorescence performance is improved.

CN119552655AActive Publication Date: 2025-03-04WENZHOU XINXIN TAIJING TECH CO LTD

Patent Information

Application Number
CN202311251027.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2025-03-04
Estimated Expiration
2043-09-26

Smart Images

  • Figure CN119552655A_ABST
    Figure CN119552655A_ABST
Patent Text Reader

Abstract

The invention provides a red light perovskite material based on bromine-iodine mixed halogen and a preparation method thereof, the red light perovskite material comprises a perovskite material doped with metal elements, the structural formula of the perovskite material is CsPbIxBr3-x, and X is more than 0 and less than 3; the doped metal element is one or more of zinc, potassium, aluminum, magnesium, calcium, strontium, barium, sodium, rubidium, lithium, cerium, samarium, antimony, erbium and bismuth; wherein the atomic percent of the cesium element is smaller than or equal to 21%, and the atomic percent of the doped metal element is larger than or equal to 10%; the red-light perovskite material only has one light-emitting peak, and the light-emitting spectrum does not move or deform under the irradiation of blue light. The prepared perovskite material is uniform in component and free of ion migration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of perovskite materials, and in particular relates to a red light perovskite material based on bromine-iodine mixed halogen and a preparation method thereof. Background Art

[0002] As a new type of luminescent material, perovskite has attracted wide attention due to its unique optical properties, such as high luminous efficiency, narrow luminescent half-width, and tunable luminescent wavelength. It can be used in display devices, light-emitting diodes, and biomedical imaging. In the field of display and luminescent applications, materials with three primary colors of red (luminescent wavelength 620-640nm), green (luminescent wavelength 520-540nm), and blue (luminescent wavelength 440-460nm) are usually required. The all-inorganic lead halide perovskite CsPbX3 (X=Cl, Br, I) material can adjust the luminescent wavelength by adjusting the composition of halogen ions, obtaining blue luminescence near 450nm in the chlorine-bromine mixed component, green luminescence near 520nm in the bromine component, and red luminescence near 625nm in the bromine-iodine component.

[0003] However, red-light emitting bromine-iodine mixed halogen inorganic lead halide perovskite usually has the following two problems in the preparation process and practical application: 1. During the preparation process, due to the difference in the reaction rate of the local precursors in the reaction container, the prepared mixed halogen perovskite composition is not uniform, resulting in a broadening of the half-width of the luminescence or even multi-peak luminescence (such as the Chinese patent with publication number CN 115224226 A). 2. In actual use, due to the presence of bromine and iodine components, the mixed halogen perovskite is prone to halogen ion migration under external environmental stimulation such as heating and strong light irradiation, resulting in a shift in the luminescence spectrum.

[0004] Therefore, developing a bromide-iodine mixed halogen-lead halide perovskite with uniform composition and no ion migration is a technical problem that needs to be solved urgently. Summary of the invention

[0005] The object of the present invention is to provide a red light perovskite material based on bromine-iodine mixed halogen and a preparation method thereof. To achieve the above object, the technical solution adopted by the present invention is:

[0006] A red light perovskite material based on bromine-iodine mixed halogen, including a perovskite material doped with a metal element, wherein the structural formula of the perovskite material is CsPbI x Br 3-x , where 0<X<3;

[0007] The doping metal element is one or more of zinc, potassium, aluminum, magnesium, calcium, strontium, barium, sodium, rubidium, lithium, cerium, samarium, antimony, erbium, and bismuth;

[0008] Wherein: the atomic percentage of cesium element is ≤21%, and the atomic percentage of doped metal element is ≥10%;

[0009] The red light perovskite material has only one luminescence peak, and the luminescence spectrum does not move or deform under blue light irradiation.

[0010] The method used in this application to determine that the luminescence spectrum has not shifted or deformed is: use 350mW / cm 2 The samples were irradiated with blue light (wavelength 450 nm) for 1 hour.

[0011] Furthermore, the atomic percentage of cesium is recorded as A, and the atomic percentage of the doped metal element is recorded as B; then: B / (A+B)=0.35-0.45.

[0012] Furthermore, the luminescence half-width of the perovskite material is less than 40nm.

[0013] Furthermore, the red light perovskite material suppresses the deformation of the luminescence spectrum caused by ion migration under blue light irradiation.

[0014] A method for preparing a red light perovskite material comprises the following steps:

[0015] S1: mixing and grinding cesium carbonate, lead halide, and a doped metal precursor to obtain a mixed powder;

[0016] S2: In an inert atmosphere, the mixed powder obtained in step S1 is calcined at a high temperature of 400-700 degrees Celsius, and then cooled to room temperature.

[0017] Preferably, the calcination temperature in step S2 is 610-700 degrees Celsius.

[0018] Furthermore, the doped metal precursor includes one or more of potassium halide, sodium halide, rubidium halide, lithium halide, zinc halide, calcium halide, barium halide, strontium halide, cerium halide, aluminum halide, samarium halide, antimony halide, erbium halide, and bismuth halide.

[0019] Furthermore, the lead halide is selected from lead bromide, lead iodide and a combination thereof, and the wavelength of red light emission can be regulated by adjusting the Br / I ratio in the lead halide.

[0020] Furthermore, the inert atmosphere is nitrogen, argon and a combination thereof, so as to protect the precursor material from being oxidized.

[0021] Furthermore, the cesium carbonate decomposes into cesium oxide at high temperature to promote the entry of doped metal ions into the structure of the perovskite material; in the perovskite material, the atomic percentage of the doped metal element is ≥10%.

[0022] Furthermore, the molar ratio of cesium carbonate: doping metal precursor=1:(0.03-0.1).

[0023] The beneficial effects of the present invention are mainly reflected in:

[0024] 1. In the prior art, the hot injection method for preparing perovskite materials usually uses cesium carbonate as the cesium source, which takes advantage of the fact that the solubility of cesium carbonate in organic solvents is greater than that of cesium halides, thereby increasing the concentration of the cesium source in the solvent. However, the temperature for synthesizing perovskite materials by the hot injection method is only in the range of 100-250°C, which is far lower than the decomposition temperature of cesium carbonate. Therefore, cesium carbonate will not be decomposed to generate cesium oxide to participate in the reaction.

[0025] In addition, cesium oxide raw materials are very easy to turn into cesium hydroxide and cesium carbonate when placed in the air. Cesium hydroxide will produce water when heated. Perovskite is an ionic compound soluble in water. Water in the precursor is not conducive to the formation of perovskite, and perovskite materials are prone to fluorescence quenching when exposed to water. Therefore, in the existing technology, cesium oxide cannot be directly added as a raw material.

[0026] The cesium source precursor selected in the present invention is cesium carbonate. Cesium carbonate is easily decomposed into carbon dioxide and cesium oxide at high temperature. Due to the chemically active properties of cesium oxide, the cesium source and metal halide are fully reacted to form perovskite, which enhances the uniformity of the solid-state reaction. The inhomogeneity of the perovskite composition caused by insufficient local reaction is avoided, and the doped metal is more easily introduced into the structure of the perovskite material.

[0027] 2. The doped metal precursor defined in the present invention is a metal halide. The easier it is for the metal halide to react with the cesium source precursor of the perovskite, the easier it is for the doped metal to enter the perovskite. The cesium source precursor of the present application is composed of cesium carbonate initially added, which is decomposed into chemically active cesium oxide under high-temperature calcination, so that with a smaller amount of doped metal precursor added (the molar ratio of cesium carbonate: doped metal precursor = 1: (0.03-0.1)), the atomic percentage of cesium element ≤ 21% and the atomic percentage of doped metal element ≥ 10% can be achieved. The metal doping efficiency of its perovskite material is significantly improved!

[0028] 3. The present invention introduces more doped metal elements (atomic percentage of doped metal elements ≥ 10%) into the perovskite material, which will simultaneously reduce the cesium content (atomic percentage of cesium elements ≤ 21%). At this time, the red light perovskite material has only one luminescence peak, and the luminescence spectrum does not move or deform under blue light irradiation, which plays a role in inhibiting the migration of halogen ions. It has the advantages of uniform composition and no ion migration. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1The photoluminescence spectra of the perovskite powders a, b, c, d, and e obtained in Example 1 of the present invention are shown;

[0030] Figure 2 Graph showing the fluorescence quantum yield (PLQY) of perovskite powders a, b, c, d, and e obtained in Example 1 of the present invention;

[0031] Figure 3 The perovskite powder b obtained in Example 1 of the present invention was heated to 350 mW / cm 2 The blue light (wavelength 450nm) was irradiated for 1 hour, and the photoluminescence spectrum before and after the blue light irradiation was obtained;

[0032] Figure 4 The photoluminescence spectra of the perovskite powders f and g obtained in Inventive Example 2;

[0033] Figure 5 The perovskite powder h obtained in Example 3 of the present invention is heated to 350 mW / cm 2 The blue light (wavelength 450nm) was irradiated for 1 hour, and the photoluminescence spectrum before and after the blue light irradiation was obtained;

[0034] Figure 6 The perovskite powder i obtained in Example 4 of the present invention was heated to 350 mW / cm 2 The blue light (wavelength 450nm) was irradiated for 1 hour, and the photoluminescence spectrum before and after the blue light irradiation was obtained;

[0035] Figure 7 The perovskite powder j obtained in Example 5 of the present invention was heated to 350 mW / cm 2 The blue light (wavelength 450nm) was irradiated for 1 hour, and the photoluminescence spectrum before and after the blue light irradiation was obtained;

[0036] Figure 8 is the photoluminescence spectrum of the perovskite powder k obtained in Example 6 of the present invention;

[0037] Fig. 9 The perovskite powder obtained in Comparative Example 2 of the present invention was heated to 350 mW / cm 2 The blue light (wavelength 450nm) was irradiated for 1 hour, and the photoluminescence spectrum before and after the blue light irradiation was obtained;

[0038] Fig.10 is the elemental energy spectrum of the perovskite material obtained in Comparative Example 2;

[0039] Fig.11 This is the elemental energy spectrum of the perovskite material obtained in Example 3. DETAILED DESCRIPTION

[0040] In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific implementation methods described herein are only used to explain the present invention and are not used to limit the present invention.

[0041] Example 1: Synthesis of CsPbI by high temperature solid state calcination 1.5 Br 1.5

[0042] Take 0.1 mol Cs2CO3, 0.2 mol PbBr2, and 0.2 mol PbI2, grind and mix them to obtain mixed powder 1.

[0043] Take 0.2 mol Cs2CO3, 0.2 mol PbBr2, and 0.2 mol PbI2, grind and mix them to obtain mixed powder 2.

[0044] Take 0.3 mol Cs2CO3, 0.2 mol PbBr2, and 0.2 mol PbI2, grind and mix them to obtain mixed powder 3.

[0045] The mixed powders 1, 2, and 3 were respectively placed in a muffle filled with argon and heated from room temperature to 610° C., and were continuously heated at 610° C. for 20 minutes, and then naturally cooled to room temperature to obtain perovskite powders a, b, and c, respectively.

[0046] The mixed powder 2 was placed in a muffle filled with argon and heated from room temperature to 400°C, and continued to be heated at 400°C for 20 minutes, and then naturally cooled to room temperature to obtain perovskite powder d.

[0047] The mixed powder 2 was placed in a muffle filled with argon and heated from room temperature to 700°C, and continued to be heated at 700°C for 20 minutes, and then naturally cooled to room temperature to obtain perovskite powder e.

[0048] Experimental analysis: The photoluminescence spectra of the perovskite powders a, b, c, d, and e obtained by sintering were tested. Their luminescence peaks were all located in the red light luminescence region of 610-650nm, and the half-height width of the luminescence was less than 40nm ( Figure 1 shown).

[0049] Take the perovskite powders a, b, c, d, and e obtained by the above sintering and test the fluorescence quantum yield (PLQY) ( Figure 2 As shown in Figure 2, the PLQY of powder b is the highest, which can reach 45%, indicating that the optimal precursor molar ratio is close to cesium / lead = 1:1, and the optimal calcination temperature is close to 610°C.

[0050] Take the perovskite powder b obtained by sintering above and use 350mW / cm 2The blue light (wavelength 450nm) was irradiated for 1 hour, and the photoluminescence spectrum ( Figure 3 As shown in the figure, the luminescence spectrum changes from a single peak to a double peak, indicating that blue light aging conditions will cause ion migration, resulting in a shift in the luminescence spectrum.

[0051] Example 2: Synthesis of CsPbIBr2 and CsPbI2Br by high temperature solid state calcination

[0052] Take 0.2 mol Cs2CO3, 0.133 mol PbBr2, and 0.267 mol PbI2, grind and mix them to obtain mixed powder 4.

[0053] Take 0.2 mol Cs2CO3, 0.267 mol PbBr2, and 0.133 mol PbI2, grind and mix them to obtain mixed powder 5.

[0054] The mixed powders 4 and 5 were placed in a muffle filled with argon and heated from room temperature to 610°C, and heated at 610°C for 20 minutes, and then naturally cooled to room temperature to obtain perovskite powders f and g, respectively.

[0055] Experimental analysis: The perovskite powders f and g obtained by sintering were taken and the photoluminescence spectra were tested. The emission peak of powder f was located in the deep red light emission region of 680nm, and the emission peak of powder g was located in the orange-red light emission region of 580nm ( Figure 4 shown).

[0056] This example illustrates that the luminescence wavelength of the obtained perovskite powder can be regulated by adjusting the bromine-iodine ratio of the precursor in the present invention.

[0057] Example 3: Synthesis of Zn by high temperature solid state calcination 2+ Doped CsPbI 1.5 Br 1.5

[0058] Take 0.2 mol Cs2CO3, 0.2 mol PbBr2, 0.2 mol PbI2, and 0.01 mol ZnBr2, grind and mix them to obtain mixed powder 6.

[0059] The mixed powder 6 was placed in a muffle filled with argon and heated from room temperature to 610°C, and was continuously heated at 610°C for 20 minutes, and then naturally cooled to room temperature to obtain perovskite powder h.

[0060] Experimental analysis: Take the perovskite powder h obtained by sintering as above and use 350mW / cm 2 The blue light (wavelength 450nm) was irradiated for 1 hour, and the photoluminescence spectrum ( Figure 5As shown in the figure, the luminescence spectrum did not shift or deform, indicating that Zn 2+ Doped CsPbI 1.5 Br 1.5 No ion migration was induced under blue light aging conditions.

[0061] Fig.11 This is the energy spectrum of the perovskite material measured by EDS. The At% distribution of each element is shown in Table 1:

[0062] Table 1

[0063] element Br Cs Pb I Zn Atomic Percentage At% 36.3% 19.5% 19.3% 11.1% 13.9%

[0064] The atomic percentage of cesium is recorded as A; the atomic percentage of the doping metal element Zn is recorded as B;

[0065] Then: B / (A+B)=0.42.

[0066] Example 4: Synthesis of K by high temperature solid state calcination 1+ Doped CsPbI 1.5 Br 1.5

[0067] Take 0.2 mol Cs2CO3, 0.2 mol PbBr2, 0.2 mol PbI2, and 0.006 mol KBr2, grind and mix them to obtain mixed powder 7.

[0068] The mixed powder 7 was placed in a muffle filled with argon and heated from room temperature to 610°C, and was continuously heated at 610°C for 20 minutes, and then naturally cooled to room temperature to obtain perovskite powder i.

[0069] Experimental analysis: Take the perovskite powder i obtained by sintering as above and use 350mW / cm 2 The blue light (wavelength 450nm) was irradiated for 1 hour, and the photoluminescence spectrum ( Figure 6 As shown in the figure, the luminescence spectrum does not move or deform, indicating that K 1+ Doped CsPbI 1.5 Br 1.5 No ion migration was induced under blue light aging conditions.

[0070] The distribution of At% of each element of the perovskite material prepared in Example 4 was measured by EDS as shown in Table 2:

[0071] Table 2

[0072] element Br Cs Pb I K Atomic Percentage At% 37.7% 20.5% 19.5% 11.3% 11.0%

[0073] The atomic percentage of cesium is recorded as A; the atomic percentage of the doping metal element K is recorded as B;

[0074] Then: B / (A+B)=0.35.

[0075] Example 5: Synthesis of Al by high temperature solid state calcination 3+ Doped CsPbI 1.5 Br 1.5

[0076] Take 0.2 mol Cs2CO3, 0.2 mol PbBr2, 0.2 mol PbI2, and 0.02 mol AlCl3, grind and mix them to obtain mixed powder 8.

[0077] The mixed powder 8 was placed in a muffle filled with argon and heated from room temperature to 610° C., and was continuously heated at 610° C. for 20 minutes, and then naturally cooled to room temperature to obtain perovskite powder j.

[0078] Experimental analysis: Take the perovskite powder j obtained by sintering as above and use 350mW / cm 2 The blue light (wavelength 450nm) was irradiated for 1 hour, and the photoluminescence spectrum ( Figure 7 As shown in the figure, the luminescence spectrum did not move or deform, indicating that Al 3+ Doped CsPbI 1.5 Br 1.5 No ion migration was induced under blue light aging conditions.

[0079] The At% distribution of each element of the perovskite material prepared in Example 5 was measured by EDS as shown in Table 3:

[0080] Table 3

[0081] element Br Cs Pb I Al Atomic Percentage At% 36.2% 18.4% 19.1% 11.4% 14.9%

[0082] The atomic percentage of cesium is recorded as A; the atomic percentage of the doping metal element Al is recorded as B;

[0083] Then: B / (A+B)=0.45.

[0084] Embodiment 6-16:

[0085] The difference from Example 3 is that the doped metal precursor is different.

[0086] Table 4: Doping metal precursors selected for Examples 6-16

[0087] Example Doping metal precursor Example 6 Sodium bromide Example 7 Rubidium Bromide Example 8 Lithium Bromide Example 9 Calcium Bromide Example 10 Barium Bromide Embodiment 11 Strontium Bromide Example 12 Cerium Bromide Embodiment 13 Samarium Bromide Embodiment 14 Antimony bromide Embodiment 15 Erbium Bromide Example 16 Bismuth Bromide

[0088] Experimental analysis: Take the perovskite powder obtained by sintering above and use 350mW / cm 2The blue light (wavelength 450nm) was irradiated for 1 hour, and the photoluminescence spectrum was tested before and after the blue light irradiation. The luminescence spectrum did not move or deform. Figure 5-7 In Examples 6-16, despite the differences in the doping metal precursors, their B / (A+B) is still within the range of 0.35-0.45.

[0089] In the above, A is the atomic percentage of cesium; B is the atomic percentage of the doping metal element.

[0090] Comparative Example 1: Synthesis of CsPbI by high temperature solid-state calcination using cesium halide as cesium source precursor 1.5 Br 1.5

[0091] Take 0.1 mol CsBr, 0.1 mol CsI, 0.1 mol PbBr2, and 0.1 mol PbI2, grind and mix them to obtain mixed powder 9.

[0092] The mixed powder 9 was placed in a muffle filled with argon and heated from room temperature to 610° C., and was continuously heated at 610° C. for 20 minutes, and then naturally cooled to room temperature to obtain perovskite powder k.

[0093] Experimental analysis: The perovskite powder k obtained by sintering was tested for photoluminescence spectrum. Its red light emission peak half-width is greater than 50nm and exhibits multi-peak emission ( Figure 8 shown).

[0094] Comparing Example 1 with Comparative Example 1, it can be shown that solid-state calcination using cesium carbonate as a precursor can make the perovskite react and synthesize more fully, which is greatly beneficial to improving the red light emitting performance of the perovskite.

[0095] Comparative Example 2:

[0096] The difference from Example 3 is that cesium carbonate is replaced by cesium halide, specifically, 0.2 mol Cs2CO3 is replaced by 0.2 mol CsBr+0.2 mol CsI.

[0097] Experimental analysis: Take the perovskite powder obtained by sintering above and use 350mW / cm 2 The blue light (wavelength 450nm) was irradiated for 1 hour, and the photoluminescence spectrum ( Fig. 9 As shown in the figure, the luminescence spectrum changes from a single peak to a double peak, indicating that blue light aging conditions will cause ion migration, resulting in a shift in the luminescence spectrum.

[0098] Fig.10 This is the energy spectrum of the perovskite material measured by EDS in Comparative Example 2. The At% distribution of each element is shown in Table 5:

[0099] Table 5

[0100] element Br Cs Pb I Zn Atomic Percentage At% 37.1% 23.8% 18.9% 11.2% 9.0%

[0101] The atomic percentage of cesium is recorded as A; the atomic percentage of the doping metal element Zn is recorded as B;

[0102] Then: B / (A+B)=0.27.

[0103] It can be seen from Example 3 and Comparative Example 2 that when cesium carbonate is selected as the cesium source and combined with a high-temperature calcination process environment, cesium carbonate is decomposed into cesium oxide to participate in the synthesis of the perovskite material, which can increase the amount of metal element doping; at the same time, the atomic percentage of the cesium element will decrease, showing a characteristic of one increasing while the other decreasing; thus, the atomic percentage of the cesium element in the perovskite material of the present invention is reduced to ≤21%, and the atomic percentage of the doped metal element is increased to ≥10%.

[0104] The embodiments described above provide a detailed description of the preparation scheme of the present invention. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the present invention. Any modifications, supplements or similar substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A red light perovskite material based on bromine-iodine mixed halogen, characterized in that: A perovskite material doped with a metal element, wherein the structural formula of the perovskite material is CsPbI x Br 3-x , where 0<X<3; The doping metal element is one or more of zinc, potassium, aluminum, magnesium, calcium, strontium, barium, sodium, rubidium, lithium, cerium, samarium, antimony, erbium, and bismuth; Wherein: the atomic percentage of cesium element is ≤21%, and the atomic percentage of doped metal element is ≥10%; The red light perovskite material has only one luminescence peak, and the luminescence spectrum does not move or deform under blue light irradiation.

2. A red light perovskite material based on bromine-iodine mixed halogen according to claim 1, characterized in that: The atomic percentage of cesium is recorded as A; the atomic percentage of the doped metal element is recorded as B; Then: B / (A+B)=0.35-0.

45.

3. The red light perovskite material based on bromine-iodine mixed halogen according to claim 1, characterized in that: The luminescence half-width of the perovskite material is less than 40nm.

4. The red light perovskite material based on bromine-iodine mixed halogen according to claim 1, characterized in that: The red light perovskite material suppresses the deformation of the light emission spectrum caused by ion migration under blue light irradiation.

5. The method for preparing the red light perovskite material according to any one of claims 1 to 4, characterized in that: The steps include: S1: mixing and grinding cesium carbonate, lead halide, and a doped metal precursor to obtain a mixed powder; S2: In an inert atmosphere, the mixed powder obtained in step S1 is calcined at a high temperature of 400-700 degrees Celsius, and then cooled to room temperature.

6. The method according to claim 5, characterized in that The doping metal precursor includes one or more of potassium halide, sodium halide, rubidium halide, lithium halide, zinc halide, calcium halide, barium halide, strontium halide, cerium halide, aluminum halide, samarium halide, antimony halide, erbium halide, and bismuth halide.

7. The method according to claim 5, characterized in that The lead halide is selected from lead bromide, lead iodide and a combination thereof, and the wavelength of red light emission can be regulated by adjusting the Br / I ratio in the lead halide.

8. The method according to claim 5, characterized in that The inert atmosphere is nitrogen, argon, or a combination thereof, which is used to protect the precursor material from being oxidized.

9. The method according to claim 5, characterized in that The cesium carbonate decomposes into cesium oxide at high temperature to promote the entry of doped metal ions into the structure of the perovskite material; in the perovskite material, the atomic percentage of the doped metal element is ≥10%.

10. The method according to claim 5, characterized in that The molar ratio of cesium carbonate: doping metal precursor=1:(0.03-0.1).

Citation Information

Patent Citations

  • Copper-doped red-light perovskite quantum dot and preparation method thereof

    CN109796976A

  • High-stability all-inorganic perovskite / aluminum phosphate composite nanomaterial and preparation method and application thereof

    CN113307303A

Cited By

  • Iodine ion doped inorganic perovskite crystal material and preparation method thereof

    CN120797202A